MENGUAK URGENSI PENDIDIKAN MODERASI BERAGAMA DI INDONESIA PERSPEKTIF ISLAM DAN BARAT DALAM MENJAWAB TANTANGAN MASA DEPAN - Dodo Suhada; Wawan Ridwan; Nurwadjah Ahmad; Andewi Suhartini; Hisam Ahyani; Naeli Mutmainah (IAIN Ambon, 2022)
In uncovering the urgency of religious moderation education in Indonesia, Islamic and western perspectives in responding to future challenges, it is important to do this, which is useful in responding to the real challenges today, namely globalization, where globalization has positive and negative effects for Muslims who Then it becomes a problem or challenge for Islamic education to overcome the negative effects and waste a generation of Muslims who are reliable in facing the challenges of globalization and identity politics. The results of the study indicate that as a solution in Responding to Indonesia's Future Challenges in the Flow of Globalization and Identity Politics through Religious Moderation Education, it can be done through the application of superior kaffah (totality) Religious Moderation Education, so that ultimately Rahmatan Lil'alamin is created in Islamic Education